2012
DOI: 10.1038/nm.2657
|View full text |Cite
|
Sign up to set email alerts
|

Commensal bacteria–derived signals regulate basophil hematopoiesis and allergic inflammation

Abstract: Commensal bacteria that colonize mammalian barrier surfaces are reported to influence T helper type 2 (TH2) cytokine–dependent inflammation and susceptibility to allergic disease, although the mechanisms that underlie these observations are poorly understood. In this report, we identify that deliberate alteration of commensal bacterial populations via oral antibiotic treatment resulted in elevated serum immunoglobulin E (IgE) levels, increased steady–state circulating basophil populations, and exaggerated baso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
338
0
7

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 413 publications
(361 citation statements)
references
References 57 publications
16
338
0
7
Order By: Relevance
“…As expected for GF conditions (16,17), serum IgE was elevated in GF-WT mice compared with CNV.WT mice, and 53BP1 deficiency suppressed this elevation (Fig. S6), consistent with the absence of cCSR in 53BP1-deficient mice.…”
Section: Significancesupporting
confidence: 84%
“…As expected for GF conditions (16,17), serum IgE was elevated in GF-WT mice compared with CNV.WT mice, and 53BP1 deficiency suppressed this elevation (Fig. S6), consistent with the absence of cCSR in 53BP1-deficient mice.…”
Section: Significancesupporting
confidence: 84%
“…In a murine model of allergic airway disease, germ-free mice exhibit more severe disease than conventionally housed controls, an effect that could be ameliorated by recolonization with conventional microbiota (57). Similar results were found when disturbance of the gut microbiome was induced by administration of antibiotics in drinking water or by an antibiotic-fungal microbiota combination (42,58). Microbial colonization early in life regulates mucosal invariant natural killer T-cell tolerance and can impact immune responses at mucosal sites later in adulthood (59).…”
Section: State Of the Art S24mentioning
confidence: 57%
“…One protocol using a cocktail of 4 antibiotics for 4-5 weeks has been exceptionally popular among investigators and allowed to demonstrate the involvement of microbiota in host functions and disease pathogenesis in a variety of models. [29][30][31][32] Furthermore, a few studies compared both germfree and antibiotic-treated animals and detected concordant results. 31,33 However, concordant results are not always observed between these 2 models.…”
Section: Introductionmentioning
confidence: 84%
“…[29][30][31][32] Furthermore, a few studies compared both germfree and antibiotic-treated animals and detected concordant results. 31,33 However, concordant results are not always observed between these 2 models. For example, in an animal model of common variable immunodeficiency (CVID) associated enteropathy (in B lymphocyte deficient mice), we found that derivation of B cell knockout (BcKO) and control mice as germfree abolished differences in the host phenotype between the 2 genotypes observed in conventional mice ( Fig.…”
Section: Introductionmentioning
confidence: 84%